Tuberculous pericarditis : experience in a community hospital - Fernando Peixoto Ferraz de Campos; Aloísio Felipe-Silva; Leonardo Gomes Fonseca; Antônio Fernando Barros de Azevedo Filho; Luiz Fernando Seguro (University of São Paulo, 2011)
Tuberculosis is a major public health problem worldwide. In Butantan district of São Paulo city, the average incidence over the last 7 years was 47.7 new cases/100,000 inhabitants. Tuberculous pericarditis is a serious form of extrapulmonary tuberculosis in which diagnosis is often difficult. Diagnosis needs to be reached fast and accurately once tuberculous pericarditis has high morbimortality rates if untreated. We report the experience of a community hospital on tuberculous pericarditis with emphasis on the clinical presentation and diagnostic procedures. From 2003 to 2010, 59 patients were diagnosed with pericarditis, 6 (10.16%) of which had tuberculous pericarditis. Demographic, clinical, imaging, laboratorial, microbiological and histological data were reviewed. There were 4 female (66.7%) and 2 male (33.3%) patients. Age ranged from 17 to 62 years (median= 25.5). One patient (17%) had HIV co-infection. Five patients (83.3%) had cardiac tamponade on Echocardiogram. Histopathology was confirmatory in 4 cases (66.7%) while cultures were positive in 2 cases (33.3%). Four patients (66.7%) had definite and 2 (33.3%) had probable diagnosis of tuberculous pericarditis. One patient (17%) died during admission. Reuter´s diagnostic index was ≥6 in 5 patients (83.3%). We concluded that the clinical picture, Reuter´s diagnostic index, signs of cardiac tamponade on Echocardiogram and the pericardium biopsy were the most important features for the diagnosis of tuberculous pericarditis.